Primary education reforms targeting marginalized groups: The role of local non-governmental organizations in slum areas in Cairo - Alaraji, Faiza (AUC Knowledge Fountain, 2016)
The Egyptian government has implemented different educational programs targeting marginalized groups in Egypt over the years. Primary education reform plans are a priority for decision makers in both developed and developing countries. Many governments paid serious attention to implement successful strategies targeting marginalized groups in their societies. The study examined in depth educational reforms strategies in the selected developed and developing countries. Special attention was devoted to examining the role of NGOs in many developing countries like Ghana, Bangladesh and Afghanistan. Civil organizations have added valuable contribution and rich experience to the field of education, especially through informal education programs targeting marginalized groups in poverty-stricken or hard-to-reach remote areas. Local NGOs in Egypt continued to serve marginalized groups through many development programs. This research covered four case studies of local NGOs in Egypt working in providing educational services to marginalized children in Greater Cairo. These NGOs are: Resala in AUC, AYB in AUC, East of Al-Maadi, and MEB. Findings of the study showed that the interviewed local NGOs helped the children to enhance their educational achievement in their public schools, encouraged them to complete their primary education successfully and empowered them with good values and self-confidence to play as elements of positive socio-economic changes in their poor communities. The study came up with a set of recommendations including the need for government cooperation with local NGOs, the need of private sector and local communities support to local NGOs to help them implement their educational programs in a better way and to achieve better results.